Anthropomorphy of sweat in reliquary guardians (Fang, Gabon): a CT scan study. (June 2020) - Jacqueline, Sophie; Moulherat, Christophe; Ordureau, Sylvain; Joubert, Hélène; Le Fur, Yves; Charlier, Philippe
Highlights: The non-invasive and non-destructive nature of the CT-scan permitted us to better understand the believes of autochthon communities. This original study of an eyema byeri and nlo byeri wooden sculpture from the Fang ethnic group allows to compare the data of the ethnological literature with new scientific data resulting from the bio-medical analyses. An artificial sweat has been forged for such artifacts in order to mimic living individuals' physiology. Abstract: For several years, the CT-scan is an indispensable tool for the study of museum objects. The CT-scan in a non-invasive and non-destructive tool that reveals internal structures of these objects. Here we present the results of 3 CT-scan of three wooden sculpture from the Fang ethnic group (Gabon, Equatorial Guinea and Cameroon), conserved in the Museum of quai Branly-Jacques Chirac (Inv. 70.2017.66.16, 70.2017.66.24, and 71.1941.13.10), Paris, France. Results put to light new data regarding the impregnation visible externally on these statues. The imbibition was progressive, and more and more important towards the outside of the statue. This interdisciplinary study of these eyema byeri or nlo byeri statue allowed us to better understand the making and use of these reliquary guardians and so put on light a part of the rites of the Fang ethnic group. This means that the anthropomorphy of sweat allows to give these statuettes the appearance of an animated body understandable by the living. More, this study highlights the interest of bio-medical analyze of tribal objects and so to better understand the magical-religious practices in autochthon communities.